The Role of Continous Ambulatory Peritoneal Dialysis in Equity of Kidney Replacement Therapy in Indonesia - Lydia, Aida (UI Scholars Hub, 2020)
With the increasing incidence of chronic kidney disease in Indonesia, an effective, sustainable and widely available kidney replacement therapy (KRT) is needed. PD is one of the available modalities that can meet those criteria. To date, out of the two existing types of PD, only continuous ambulatory peritoneal dialysis (CAPD) is available in our country. Studies showed that residual kidney function is preserved better in CAPD patients compared to HD patients. With the use of CAPD as KRT, patients can do dialysis independently. Hence, it can be solution to the limitations and the difficulty of reaching HD units especially in remote areas. However, due to lack of knowledge or experience of clinicians regarding CAPD, the use of CAPD is scarce in Indonesia. Clinicians can increase their role in kidney services by increasing CAPD utilization. The key to improve CAPD utilization is a good understanding and optimal education about CAPD to patients and their families. This review aims to introduce and remind clinicians of the availability of CAPD besides HD and kidney transplant as one of the available modalities of KRT for patients with ESKD in Indonesia.